Fishing for answers? Impacts of marine ecosystem quality on coastal tourism demand. Issue 5 (August 2017) - Otrachshenko, Vladimir; Bosello, Francesco
This article examines the impact of marine ecosystem quality on inbound coastal tourism in the Baltic, North Sea, and Mediterranean countries. Using marine protected areas (MPAs) and the fraction of overexploited species as a proxy for marine ecosystem quality, we apply an autoregressive distributed lag model in a destination–origin panel setup. The empirical findings suggest that the presence of MPAs and the fraction of overexploited species have a considerable impact on inbound coastal tourism. Moreover, the impact of the overexploitation index on tourism is persistent and its short-term (current) impact constitutes 65% of the long-term impact. The results underscore the importance of marine ecosystem quality for inbound coastal tourism and its overall impact that may exceed the impact of tourists' income. We also find that government performance is crucial for inbound tourism.